2014
DOI: 10.1111/php.12235
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Metal Ion Functionalized NaY Zeolite

Abstract: A series of luminescent ion exchanged zeolite are synthesized by introducing various ions into NaY zeolite. Monometal ion (Eu(3+), Tb(3+), Ce(3+), Y(3+), Zn(2+), Cd(2+), Cu(2+)) exchanged zeolite, rare-earth ion (Eu(3+), Tb(3+), Ce(3+)) exchanged zeolite modified with Y(3+) and rare-earth ion (Eu(3+), Tb(3+), Ce(3+)) exchanged zeolite modified with Zn(2+) are discussed here. The resulting materials are characterized by Fourier transform infrared spectrum radiometer (FTIR), XRD, scanning electronic microscope (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…And the number and sites of the cations strongly affect the properties of the zeolites. Among all kinds of zeolites, zeolite-Y shows the faujasite (FAU) structure, whose pore diameter is about 7.4 Å as the aperture is defined by a 12-member oxygen ring resulting in a larger cavity diameter of 12 Å1.…”
mentioning
confidence: 99%
“…And the number and sites of the cations strongly affect the properties of the zeolites. Among all kinds of zeolites, zeolite-Y shows the faujasite (FAU) structure, whose pore diameter is about 7.4 Å as the aperture is defined by a 12-member oxygen ring resulting in a larger cavity diameter of 12 Å1.…”
mentioning
confidence: 99%
“…It is due to the 4f 0 5d 1 → 4f 1 5d 0 transition in Ce 3+ . This transition is from the excited state, 2 D 3/2 , to either the 2 F 7/2 state or the 2 F 5/2 ground state; these cannot be distinguished directly . Although the dehydration of the powder caused many water molecules bound to Ce 3+ to be lost, the emission peak position at 347 nm is almost the same as it was in hydrated Ce,Na–Y, 350 nm. , Suib and Tanguay suggested that most dehydrated rare earth exchanged zeolites show extremely broadened emission spectra because of the loss of water molecules and the movement of Ce 3+ ions into the sodalite cavities …”
Section: Discussionmentioning
confidence: 99%
“…36 Although the dehydration of the powder caused many water molecules bound to Ce 3+ to be lost, the emission peak position at 347 nm is almost the same as it was in hydrated Ce,Na−Y, 350 nm. 36,37 Suib and Tanguay suggested that most dehydrated rare earth exchanged zeolites show extremely broadened emission spectra because of the loss of water molecules and the movement of Ce 3+ ions into the sodalite cavities. 37 The luminescence results may not be directly related to the structure reported because the powder (Si/Al ca.…”
Section: Trigonal and Octahedralmentioning
confidence: 90%
See 2 more Smart Citations